CCR3 deficiency shifts adaptive to innate-driven immunity in asthma - Krammer, Susanne; Yang, Zuqin; Mitländer, Hannah; Grund, Janina; Geppert, Carol-Immanuel; Rieker, Ralf; Zirlik, Sabine; Finotto, Susetta (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Because of repeated contact with airborne allergens, patients suffering from allergic asthma experience acute asthma attacks, characterized by shortness of breath, chest tightness, and coughing. The underlying immune response is highly complex and involves various immune cells. Chemokines play a pivotal role in the appropriate relocation of these diverse immune cells, ensuring their directed migration to the site of inflammation, their survival, and their effector functions. In the context of allergic asthma, the chemokine receptor CCR3 is crucially involved in TH2-mediated airway inflammation by recruiting eosinophils and other immune cells to the site of inflammation. However, more recent studies demonstrate its presence also on mast cells, macrophages, T cells, and dendritic cells. Objective: We sought to investigate the role of CCR3 in different immune cell types during asthma pathogenesis. Methods: Human peripheral blood cells collected from healthy controls and asthmatic individuals were analyzed for CCR3 expression. A murine model of asthma was used to compare wild-type and CCR3-deficient mice in the context of airway inflammation. Results: In a human cohort of asthmatic patients, CCR3 mRNA expression was found induced in PBMCs and positively correlated with decreased lung function and blood eosinophilia. In a murine model of disease, CCR3 was found to be important for the establishment of eosinophilic inflammation. Moreover, CCR3-deficient mice showed impaired cytokine release, resulting in an innate-like mast cell and neutrophil-mediated lung inflammation and reduced TH2-orchestrated eosinophil-driven asthma. In the absence of CCR3, CD8 T cells underwent phenotypic changes, inhibiting the development of migratory effector memory CD8 T-cell subsets. Conclusions: Taken together, this work demonstrates the functional involvement of CCR3 in both innate and adaptive immune cells in the lung during asthma pathogenesis.
CRIS-Team Scopus Importer:2025-03-14
Keywords: asthma; CD8; Chemokines; eosinophils; neutrophils

Corrigendum: Mechanism of Rhinovirus Immunity and Asthma, (Front. Immunol, (2021), 12, (731846), 10.3389/fimmu.2021.731846) - Yang, Zuqin; Mitländer, Hannah; Vuorinen, Tytti; Finotto, Susetta (Frontiers in Immunology, 2021)
In the original article, the authors neglected to include the funder Collaborative Research Centre (CRC) 1181 (Erlangen), grant number TP-B08 N to authors Zuqin Yang and Susetta Finotto. In the original article, there was an error. The scientific meaning of the following sentence was unclear owing to poor syntax: “In asthma, are predominantly induced ILC2 producing type 2 cytokine IL-4, IL-5, IL-13, and IL-9”. A correction has been made to Innate Immune Response in Asthma, Innate Lymphoid Cells (ILC2), Paragraph 1. The sentence should read: “In asthma, ILC2 producing type 2 cytokine IL-4, IL-5, IL-13, and IL-9 are predominantly induced”. The same is true of the following sentence: “After RV16 infection, in Tregs were induced both in healthy control and asthmatic subjects with upregulated anti-viral gene expression, such as IFI44L, MX1, ISG15, IRF and STAT1”. A correction has been made to Adaptive Immune Response in Asthma, Treg, Paragraph 2. The sentence should read: “After RV16 infection, Tregs were induced both in healthy control and asthmatic subjects with upregulated anti-viral gene expression, such as IFI44L, MX1, ISG15, IRF and STAT1”. The authors apologize for these errors and state that they do not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2021-12-17
Keywords: asthma; host defense; immune evasion; interferon type I; rhinovirus

Expression of IFN lambda and its receptor in human adult asthma cohort AZCRA - Krammer, Susanne; Yang, Zuqin; Gutu, Sicorschi C.; Grund, Janina; Mitländer, Hannah; Zirlik, Sabine; Finotto, Susetta (ALLERGY, 2021)
CRIS-Team WoS Importer:2021-12-03

Mechanism of Rhinovirus Immunity and Asthma - Yang, Zuqin; Mitländer, Hannah; Vuorinen, Tytti; Finotto, Susetta (Frontiers in Immunology, 2021)
The majority of asthma exacerbations in children are caused by Rhinovirus (RV), a positive sense single stranded RNA virus of the Picornavirus family. The host has developed virus defense mechanisms that are mediated by the upregulation of interferon-activated signaling. However, the virus evades the immune system by inducing immunosuppressive cytokines and surface molecules like programmed cell death protein 1 (PD-1) and its ligand (PD-L1) on immunocompetent cells. Initially, RV infects epithelial cells, which constitute a physiologic mucosal barrier. Upon virus entrance, the host cell immediately recognizes viral components like dsRNA, ssRNA, viral glycoproteins or CpG-DNA by host pattern recognition receptors (PRRs). Activation of toll like receptors (TLR) 3, 7 and 8 within the endosome and through MDA-5 and RIG-I in the cytosol leads to the production of interferon (IFN) type I and other antiviral agents. Every cell type expresses IFNAR1/IFNAR2 receptors thus allowing a generalized antiviral activity of IFN type I resulting in the inhibition of viral replication in infected cells and preventing viral spread to non-infected cells. Among immune evasion mechanisms of the virus, there is downregulation of IFN type I and its receptor as well as induction of the immunosuppressive cytokine TGF-β. TGF-β promotes viral replication and is associated with induction of the immunosuppression signature markers LAP3, IDO and PD-L1. This article reviews the recent advances on the regulation of interferon type I expression in association with RV infection in asthmatics and the immunosuppression induced by the virus.
CRIS-Team Scopus Importer:2021-10-29
Keywords: asthma; host defense; immune evasion; interferon type I; rhinovirus

NFATc1 in CD4+ T cells and CD11c+ dendritic cells drives TH2-mediated eosinophilic inflammation in allergic asthma - Yang, Zuqin; Krammer, Susanne; Mitländer, Hannah; Grund, Janina; Zirlik, Sabine; Wirtz, Stefan; Rauh, Manfred; Sadeghi Shermeh, Atefeh; Finotto, Susetta (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Asthma, a chronic lung disease, is a significant public health problem worldwide. It is marked by increased TH2 response resulting in eosinophil accumulation. The pathophysiology of asthma involves various cell types, including epithelial cells, dendritic cells (DCs), innate lymphoid cells, B cells, and effector cells. Nuclear factor of activated T cells, cytoplasmic 1 (NFATc1), a critical transcription factor for immune regulation, is known for its role in T cells and, more recently, in myeloid cells. However, the specific contributions of NFATc1 in T cells and DCs in the context of asthma are not well understood. Objective: We explored NFATc1’s role in T cells and DCs in modulating TH2 immune responses within the pathophysiology of allergic asthma. Methods: We induced asthma in mice lacking Nfatc1 in CD4+ T cells or CD11c+ DCs using house dust mite, thereby enabling investigation into NFATc1’s role in both cell types in experimental allergic asthma. Additionally, we examined NFATc1 expression in these cell types and its correlation with blood eosinophil levels in an adult asthma cohort. Results: In a house dust mite–induced asthma model, we found that Nfatc1 deficiency either in CD4+ T cells or CD11c+ DCs resulted in reduced TH2-driven eosinophilic inflammation, IgE levels, and mast cell presence in the lung of asthmatic mice. Nfatc1’s absence in CD4+ T cells directly hampered TH2 cell polarization and functionality, whereas in CD11c+ DCs, it affected DC differentiation and maturation, thereby weakening T-cell priming, proliferation, and subsequent TH2 differentiation. Correspondingly, translational research indicated significant correlations between CD4+NFATc1+ and CD11c+NFATc1+ cell populations and eosinophil levels in asthmatic patients, but not in healthy controls. Conclusion: NFATc1 in T cells and DCs modulates TH2-mediated eosinophilic inflammation in allergic asthma, thus offering insight into asthma pathogenesis and identifying NFATc1 as a potential target for therapeutic intervention.
CRIS-Team Scopus Importer:2024-11-15
Keywords: allergic asthma; dendritic cells; eosinophils; NFATc1; T cells; T

Poly I:C Pre-Treatment Induced the Anti-Viral Interferon Response in Airway Epithelial Cells - Mitländer, Hannah; Yang, Zuqin; Krammer, Susanne; Grund, Janina; Zirlik, Sabine; Finotto, Susetta (Viruses, 2023)
Type I and III interferons are among the most important antiviral mediators. Increased susceptibility to infections has been described as being associated with impaired interferon response in asthmatic patients. In this work, we focused on the modulation of interferon dysfunction after the rhinovirus infection of airway epithelial cells. Therefore, we tested polyinosinic:polycytidylic acid (poly I:C), a TLR3 agonist, as a possible preventive pre-treatment to improve this anti-viral response. In our human study on asthma, we found a deficiency in interferon levels in the nasal epithelial cells (NEC) from asthmatics at homeostatic level and after RV infection, which might contribute to frequent airway infection seen in asthmatic patients compared to healthy controls. Finally, pre-treatment with the immunomodulatory substance poly I:C before RV infection restored IFN responses in airway epithelial cells. Altogether, we consider poly I:C pre-treatment as a promising strategy for the induction of interferon response prior to viral infections. These results might help to improve current therapeutic strategies for allergic asthma exacerbations.
Created from Fastlane, Scopus look-up
Keywords: asthma; epithelial cells; interferons; poly I:C; rhinovirus

Rhinovirus Suppresses TGF-β-GARP Presentation by Peripheral NK Cells - Krammer, Susanne; Yang, Zuqin; Mitländer, Hannah; Grund, Janina; Trump, Sonja; Mittler, Susanne; Zirlik, Sabine; Neurath-Finotto, Susetta (Cells, 2023)
Asthma is a chronic airway disease whose exacerbations are often triggered by rhinovirus infection. TGF-β1 induces rhinovirus replication in infected cells. Moreover, TGF-β1 is a pleiotropic mediator that is produced by many immune cells in the latent, inactive form bound to the latency-associated peptide (LAP) and to the transmembrane protein glycoprotein A repetitions predominant (GARP). In this study we wanted to investigate the effect of rhinovirus infection on the TGF-β secretion and the downstream signaling via TGF-βRI/RII in peripheral blood mononuclear cells from control and asthmatic patients after rhinovirus infection ex vivo. Here, we found a significant upregulation of TGF-βRII in untouched PBMCs of asthmatics as well as a suppression of TGF-β release in the rhinovirus-infected PBMC condition. Moreover, consistent with an effect of TGF-β on Tregs, PBMCs infected with RV induced Tregs, and TGF-βRII directly correlated with RV1b mRNA. Finally, we found via flow cytometry that NK cells expressed less GARP surface-bound TGF-β, while cytokine-producing NKbright cells were induced. In summary, we show that rhinovirus infection inhibits TGF-β release in PBMCs, which results in the activation of both Treg and NK cells.
CRIS-Team Scopus Importer:2023-01-20
Keywords: asthma; NK cells; rhinovirus; TGF-β; TGF-β RI; TGF-β RII

Vitamin D3 resolved human and experimental asthma via B lymphocyte-induced maturation protein 1 in T cells and innate lymphoid cells. - Grund, Janina; Krammer, Susanne; Yang, Zuqin; Mitländer, Hannah; Rauh, Manfred; Zirlik, Sabine; Kiefer, Alexander; Zimmermann, Theodor; Rieker, Ralf; Geppert, Carol-Immanuel; Papadopoulos, Nikolaos G.; Neurath-Finotto, Susetta (Journal of Allergy and Clinical Immunology: Global, 2023)
BACKGROUND: Vitamin D3 (VitD3) is known to have immunomodulatory functions, and VitD3 deficiency is associated with more severe asthma. OBJECTIVE: We aimed to assess the immunoregulatory effects of VitD3 food supplementation on asthma manifestation, with particular focus on T cells and type 2 innate lymphoid cells. METHODS: Preschool children and adult asthmatic cohorts were analyzed in the context of VitD3 supplementation and serum levels. In a murine model of ovalbumin-induced asthma, effects of diet VitD3 sufficiency and deficiency on T cells and type 2 innate lymphoid cells immune mechanisms were investigated. RESULTS: We found less severe and better-controlled asthma phenotypes along with reduced need for steroid medication in preschool children and asthmatic adults with VitD3 supplementation. VitD3 serum levels correlated with B lymphocyte-induced maturation protein 1 (Blimp-1) expression in blood peripheral mononuclear cells. VitD3-supplement-fed mice showed decreased asthmatic traits, with a decrease in IgE serum levels, reduced airway mucus, and increased IL-10 production by lung cells. Furthermore, we discovered an upregulation of effector T cells and Blimp-1+ lung tissue-resident memory T cells as well as induction of anti-inflammatory Blimp-1+ lung innate lymphoid cells producing IL-10. CONCLUSION: Supplementing VitD3 resulted in amelioration of clinical asthma manifestations in human studies as well as in experimental allergic asthma, indicating that VitD3 shifts proinflammatory immune responses to anti-inflammatory immune responses via upregulating Blimp-1 in lung innate lymphoid cells and tissue-resident memory cells.
EVALuna2:544627
Keywords: Allergic asthma; pediatric asthma; adult asthma; vitamin D3; vitamin D3 supplementation; TRM; ILC2s; Blimp-1; resolution of asthma